The relation between children abuse and the level of incurred traumas - Pakalniškienė, Vilmantė; Bieliauskaitė, Rasa; Sebre, Sandra (Psichologija, 2003)
This study was designed to look at levels of incidence of child emotional, physical and sexual abuse, associated risk factors and trauma symptoms in a crosscultural comparison between two Baltic countries. Six hundred six chilren ages 10-14 from Latvia (306), Lithuania (300) participated in the study. They were assessed by questionnaires concerning experience of emotional, physical or sexual abuse. The children also responded to questionnaire items concerning parental risk-factors and trauma symptoms: depression, anxiety, anger, PTSD, dissociation, sexual concerns and psychosomatic complaints. Levels of reported incidence of emotional, physical and sexual abuse differed by country, as did levels of reported trauma symptoms. Incidence of emotional and physical abuse differed by region, with higher levels of abuse reported in the rural regions. In both countries generally similar levels of high association between emotional/physical abuse and trauma symptoms were found. Children who had experienced abuse possess more traumatic symptoms rather than those who had not experience the abuse; self assessment of children who experience abuse is lower; there are substantial differences between data from Lithuania and from Latvia, children in Lithuania much more often dream and fantasize and tend to dissociate themselves from unpleasant experience.
Keywords: children abuse; level of incurred traumas